# Factor the polynomial: x3−4x2−9x+36

burkinaval1b

## Answered question

2021-12-09

Factor the polynomial:

${x}^{3}-4{x}^{2}-9x+36$

### Answer & Explanation

Step 1

Given,

${x}^{3}-4{x}^{2}-9x+36$

Step 2

On simplification, we get

$\Rightarrow {x}^{2}(x-4)-9(x-4)$

$\Rightarrow (x-4)({x}^{2}-9)$

$\Rightarrow (x-4)({x}^{2}-{3}^{2})$

$\Rightarrow (x-4)(x-3)(x+3)\text{}\text{}\text{}[\because {a}^{2}-{b}^{2}=(a+b)(a-b)]$

Do you have a similar question?

Recalculate according to your conditions!